Consuming Ecstasy: Representations of Male and Female Orgasm in Mainstream Pornography - Séguin, Léa J.; Rodrigue, Carl; Lavigne, Julie (The Journal of Sex Research, 2018)
Social representations, which appear in a variety of media, can influence the way sexual experiences are perceived and understood. While pornography is not the only medium in which orgasm is portrayed, it is the most explicit, and it is widespread and easily accessible. As such, pornography is an ideal medium for examining representations of male and female orgasm. PornHub’s 50 most viewed videos of all time were viewed and coded for the frequency of male and female orgasm, orgasm-inducing sex acts (and whether activity inducing female orgasms included some form of clitoral stimulation), and auditory (verbal, vocal) and visual (bodily) indicators of orgasm. Content analysis was used to code and analyze the data. Results were analyzed in light of sexual script theory and previous orgasm research. Only 18.3% of women, compared to 78.0% of men, were shown reaching orgasm. Sex differences in depictions of orgasm, beyond the appearance of semen, were documented. Results support the male performance script as evident in pornographic depictions of orgasm, as well as coital and orgasm imperatives. As a result, representations of male and female orgasm in mainstream pornography may serve to perpetuate unrealistic beliefs and expectations in relation to female orgasm and male sexual performance.
Keywords: 2000 à aujourd'hui; 2010-2019; approches et analyses; cours; discipline; orgasme; premier cycle; périodes historiques; rapports sociaux de sexe; représentation; ressource en ligne; sciences humaines; sex1911; sexologie; sexualité; thématiques

Représentations de l’intimité hétérosexuelle et transformations sociales: vers une sémantique amoureuse intégrée - Piazzesi, Chiara; Blais, Martin; Lavigne, Julie; Lavoie-Mongrain, Catherine; Renière, Roxane (Sociologie et sociétés, 2018)
Il existe trois positions principales dans la littérature sociologique occidentale sur les transformations de l’intimité et des imaginaires amoureux contemporains : la thèse de l’individualisation comme émancipation de la tradition, la thèse de la détraditionnalisation comme déliaison et la thèse de la coexistence entre tradition et modernisation dans les discours et les pratiques intimes. À partir d’une étude de cas sur la télésérie québécoise La Galère (2007-2013), cet article propose une quatrième approche pour aborder ces transformations qui permet de dépasser les limites théoriques et empiriques des trois positions mentionnées. Cette approche développe le concept de « sémantique intégrée » pour décrire en détail les éléments des sémantiques en circulation dans les produits culturels occidentaux, ainsi que les modalités de la coexistence entre imaginaires traditionnels et imaginaires novateurs. De plus, cette approche offre des outils conceptuels pour formuler des hypothèses sur la relation entre les évolutions sémantiques et les transformations sociales contemporaines dans la sphère intime.
Keywords: 2000 à aujourd'hui; 2000-2009; 2010-2019; amour; amérique du nord; amériques; approches et analyses; canada; care; corps; couple; cours; discipline; hétérosexualité; premier cycle; périodes historiques; québec; relations amoureuses; régions géographiques; sciences humaines; sexualité; soc2264; sociologie; thématiques